2013
DOI: 10.1007/s12253-013-9716-z
|View full text |Cite
|
Sign up to set email alerts
|

ZFP91—A Newly Described Gene Potentially Involved in Prostate Pathology

Abstract: In search for novel molecular targets in benign prostate hyperplasia (BPH), a PCR Array based screening of 84 genes was performed. Of those, expression of ZFP91 (ZFP91 zinc finger protein) was notably upregulated. Limited data concerning the function of ZFP91 product show that it is a potential transcription factor upregulated in human acute myelogenous leukemia and most recently found to be the non-canonical NF-κB pathway regulator. In order to test this finding on a larger number of samples, prostate specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Analyses were performed as described earlier [2, 18, 19]. Briefly, primers were designed by Primer 3 software (Whitehead Institute for Biomedical Research, Cambridge, USA) and purchased from the Laboratory of DNA Sequencing and Oligonucleotide Synthesis (Institute of Biochemistry and Biophysics, Polish Academy of Sciences, Warsaw, Poland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses were performed as described earlier [2, 18, 19]. Briefly, primers were designed by Primer 3 software (Whitehead Institute for Biomedical Research, Cambridge, USA) and purchased from the Laboratory of DNA Sequencing and Oligonucleotide Synthesis (Institute of Biochemistry and Biophysics, Polish Academy of Sciences, Warsaw, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…Still novel targets are being searched to aid in diagnosis and treatment of this complex and heterogeneous disease [1]. In 2014 our team described changes in expression of little-studied ZFP91 zinc finger protein gene ( ZFP91 ) in benign prostate hyperplasia (BPH) and in prostate cancer cell lines [2]. Recently found oncogenic properties of this gene prompted us to further study its significance in prostate cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ZFP91 interacts with ARF tumor suppressor (cyclin-dependent kinase inhibitor 2A), which is known for its induction of p53-dependent cell death or growth arrest in response to activated oncogenes [2]. Furthermore, ZFP91 plays a critical role in acute myelogenous leukemia and prostate pathology [3, 4]. Our previous study indicated that ZFP91 is an atypical E3 ligase activating NF-κB-inducing kinase (NIK) via Lys 63 -linked ubiquitination in the noncanonical NF-κB signaling pathway [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…To validate the obtained results in an another manner, we used commercially available primers, which, however, yielded false positive results: with 'PPH01112A for human HCRTR1' primer, reaction products of the size of approximately 100 bp were observed in all studied human prostatic cell lines as well as in negative controls (-RT). Therefore, we are not surprised by results obtained by means of Human Obesity RT2 Profiler PCR Array (SuperArrayBioscience; SABioscience) applied by us in studies on OXR1 expression in normal human prostate and benign prostate hyperplasia [29]. In these studies we demonstrated reaction products for OXR1; however, the primers applied were the same, as purchased for the present study.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, in our earlier QPCR study we were unable to demonstrate expression of ppOX in human normal and hyperplastic prostate [16]. Likewise, in our recent microarray study (Human Obesity RT2 Profiler PCR Array, Qiagen) we were unable to demonstrate expression of ppOX in both normal human prostate gland and benign prostate hyperplasia [29].…”
Section: Discussionmentioning
confidence: 57%